2014
DOI: 10.1007/s12275-014-4300-0
|View full text |Cite
|
Sign up to set email alerts
|

Anti-influenza effect of Cordyceps militaris through immunomodulation in a DBA/2 mouse model

Abstract: The immune-modulatory as well as anti-influenza effects of Cordyceps extract were investigated using a DBA/2 mouse model. Three different concentrations of Cordyceps extract, red ginseng extract, or drinking water were orally administered to mice for seven days, and then the mice were intranasally infected with 2009 pandemic influenza H1N1 virus. Body weight changes and survival rate were measured daily post-infection. Plasma IL-12, TNF-α, and the frequency of natural killer (NK) cells were measured on day 4 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…The cultured mycelium Cordyceps sinensis (CMCS), a Chinese herbal medicine, is capable of inhibiting inflammation and regulating the immune system [17] . The number and cytotoxicity of NK cells have been reported to increase significantly in response to C. sinensis both in vitro and in vivo [18][19][20] . Our previous study revealed that CMCS could inhibit liver fibrosis and had no nocuous effects on normal tissues [21,22] .…”
Section: Introductionmentioning
confidence: 99%
“…The cultured mycelium Cordyceps sinensis (CMCS), a Chinese herbal medicine, is capable of inhibiting inflammation and regulating the immune system [17] . The number and cytotoxicity of NK cells have been reported to increase significantly in response to C. sinensis both in vitro and in vivo [18][19][20] . Our previous study revealed that CMCS could inhibit liver fibrosis and had no nocuous effects on normal tissues [21,22] .…”
Section: Introductionmentioning
confidence: 99%
“…The chemical composition polysaccharides, total polyphenol and total flavonoids were greater in fresh C. militaris than dried C. militaris; adenosine and cordycepin in fresh C. militaris and dried C. militaris were nearly the same C. militaris extract Provided by dong-a pharm. Co., LTD. (korea) C in health mice (Lee et al, 2014) IL-12 ↑ in plasma and NK cells population ↑ in peripheral blood C in H1N1 infected mice model 1. mortality ↓ 2. IL-12 ↑ and TNF-α ↓ Dried C. militaris 50% ethanol at room temperature and at normal pressure for 3 days 1.…”
Section: Origin Extracting Methods Function and Possible Mechanism Refmentioning
confidence: 99%
“…In China, C. militaris is also known as ‘North DongChongXiaCao’ and ‘BeiChongCao’ (means northern cordyceps). Recent studies have demonstrated that C. militaris has multiple pharmacological activities such as anti-tumour (Jin et al 2008), anti-influenza virus (Lee et al 2014), irradiation protective (Jeong et al 2014) and anti-inflammatory (Smiderle et al 2014). C. militaris has been increasingly viewed as a substitute for Chinese cordyceps in traditional Chinese medicine and health foods because of their similar chemical profiles and medicinal properties (Gao and Wang 2008; Yue et al 2008; Dong et al 2012).…”
Section: Industry Of Fungi Associated With Chinese Cordycepsmentioning
confidence: 99%